2015
DOI: 10.1007/s12237-015-9952-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Occurrence Patterns of Young Sharks in Tropical Coastal Waters

Abstract: Understanding spatio-temporal patterns in shark occurrence is critical for assessing the ecological role of a species, its vulnerability to human impacts and environmental change, and the efficacy of conservation and management strategies. Investigating these patterns can also develop an understanding of the functioning of coastal shark nurseries. In this context, we undertook a multi-year fisheries-independent survey of shark occurrence along a 400-km stretch of tropical coastline. Logistic regression was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
1
4
0
1
Order By: Relevance
“…Northern Australia has a comparatively high elasmobranch biodiversity that includes many large‐bodied and highly mobile species (Last & Stevens, 2009). Variability in species composition is not only influenced by regional conditions, but also reflects the complex life‐history strategies of many elasmobranchs that includes behaviour such as inshore nursery usage (Simpfendorfer & Milward, 1993; Yates, Heupel, Tobin, Moore, et al., 2015; Yates et al., 2015b), partitioning by size and sex (Knip et al., 2012; Yates, Heupel, Tobin, Moore, et al., 2015), and seasonal migration between tropical and temperate waters (Braccini et al., 2018; Heupel et al., 2015). Disentangling such patterns is beyond the capability of presence–absence data alone; however, these data can nonetheless assist in corroborating existing patterns in composition as well as identify new ones.…”
Section: Discussionmentioning
confidence: 99%
“…Northern Australia has a comparatively high elasmobranch biodiversity that includes many large‐bodied and highly mobile species (Last & Stevens, 2009). Variability in species composition is not only influenced by regional conditions, but also reflects the complex life‐history strategies of many elasmobranchs that includes behaviour such as inshore nursery usage (Simpfendorfer & Milward, 1993; Yates, Heupel, Tobin, Moore, et al., 2015; Yates et al., 2015b), partitioning by size and sex (Knip et al., 2012; Yates, Heupel, Tobin, Moore, et al., 2015), and seasonal migration between tropical and temperate waters (Braccini et al., 2018; Heupel et al., 2015). Disentangling such patterns is beyond the capability of presence–absence data alone; however, these data can nonetheless assist in corroborating existing patterns in composition as well as identify new ones.…”
Section: Discussionmentioning
confidence: 99%
“…Large, adult C. limbatus, which are clearly separable from C. tilstoni have been reported in small numbers throughout northern Australia (Stevens and Wiley 1986;Salini et al 2007;Johnson et al 2017). Neonate C. limbatus, also easily separable (Harry et al 2012), have been reported from communal shark nursery areas on both the east and west coasts of Australia (Simpfendorfer and Milward 1993;White and Potter 2004;Gutteridge 2011;Taylor and Bennett 2013;Yates et al 2015).…”
Section: Additional Discussion Points On the Ecology Of Central Eastementioning
confidence: 99%
“…This establishes the coastal embayment's role as critical wet season habitat for G. glyphis, while also highlighting the importance of Tentpole and Hudson Creeks as important dry season habitat. Temporal partitioning of habitat has been shown previously in other euryhaline elasmobranches (Heupel and Simpfendorfer 2008, Whitty et al 2009, Yates et al 2015). This ability of biotelemetry to obtain long-term and relatively unbiased location information highlights its capacity to identify threats and inform the spatial and temporal scale of management actions for mobile aquatic species.…”
Section: Discussionsupporting
confidence: 63%